Determinants of Capital Structure of UK Firms - Wu, Meiying (2010)
This paper aims to investigate the determinants of capital structure of UK firms and identify which existing theory of capital structure is most relevant and applicable to UK firms. The sample of this study involves 239 listed firms from 9 industries on the FTSE 350 Index in the UK from 2000 to 2009. ANOVA and panel data regression are run to analyze what factors have impact on firm’s decision of capital structure. Each test is run on long-term and short-term leverage as dependent variables. Size, tangibility, profitability, effective tax rate, non-debt tax shields, growth opportunity, share price performance and industry classification are determined as independent variables. Based on our study, most of determinants follow the prediction of trade-off theory. Size, tangibility, profitability, non-debt tax shields, industry classification and share price performance are proved to have significantly impact on leverage level. On the contrary, effective tax rate and growth opportunity do not have any explanation power for UK firm’s financing choices. More precisely, there is no evidence supporting any single theory that can explain the UK firms’ capital structure decisions. Thus, the determinants still remain a puzzle.